Realizing Restorative Justice Through Rehabilitation For Narcotics Abuse As An Implementation Of The Principle Of Dominus Litis - Dede Kania; Litya Surisdani Anggraeniko (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
Rehabilitation is one form of restorative justice in Indonesia's criminal justice system. The rehabilitation practice is also able to reach drug abusers. The condition of correctional institutions that are overcapacity is the reason for the importance of alternative punishment for narcotics cases. On the other hand, narcotics are the category of victimless crimes, so the victims and perpetrators must be protected to reduce other impacts. This research uses the juridical-normative method by studying legislation and principles of criminal law. The results represent that the prosecutor's office has an important role in realising restorative justice in drug cases based on the dominus Litis principle. The use of rehabilitation is limited to drug abusers who commit criminal acts against themselves. It is still necessary to reorient the policy of terminating cases of narcotics abuse by the prosecutor's office so that the implementation of rehabilitation is truly compatible with the principle of victim protection in punishment.